A Nonlinear Programming Technique for the Optimization of Continuous Processing Systems - Griffith, R. E.; Stewart, R. A. (Management Science, 1961)
A description is given of a method for solving some nonlinear programming problems. The mathematics of this method are quite simple and are easy to apply to electronic computation. A numerical example, a model construction example, and a description of a particular existing computer system are included in order to clarify the mode of operation of the method.